Fruit drop and bloom return according to time of metyamitron application for chemical thinning in 'Red Chief' apple - Curetti, Mariela (2022)
Trabajo presentado al EUFRIN Fruit Thinning Working Group Symposium. Belgrade (Serbia), febrero 2020